KONTEN TIKTOK DARI PERSPEKTIF ORANG TUA TERHADAP PERILAKU MENYIMPANG SISWA SMP NEGERI 3 DENPASAR - Siagian, Edy Diyana; Zuryani, Nazrina; Aditya, I Gusti Ngurah Agung Krisna (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
The influence of technological advances this extends to all aspects of human life is very significant. Everything in today's digital era based on technology. One of the most important needs for everyone nowadays is access to media. TikTok is a popular social networking platform that is wiedly used. In the worst case, TikTok causes harm to its users. SMP N 3 Denpasar is one of the schools where students use the TikTok application a lot. The research uses descriptive and explanatory strategies and it is a qualitative research method. In addition, this study also uses quantitative research techniques. The purpose of this research is to show the importance for parents to exercise social control and set time limits based on logical reasoning and regulate the use of the TikTok program in order to reduce the negative impact of the TikTok.